Revealing the Framing of the Kanjuruhan Tragedy-Themed Poems in the Jawa Pos Digital Media: Ontological, Epistemological, and Axiological Perspectives - Annisa Rizky Fadilla; Anwar Efendi; Hartono Hartono; Esti Swatika Sari (Indonesian Journal of EFL and Linguistics, 2023)
The digitalization era considers the media an urgent influencer for various aspects of life. The media's perspective also shapes perspectives and even influences decision-making for the community. Every media has an ideology. Framing analysis is intended to dissect the ideology of the media when constructing facts. On the other hand, the spread of digital media has impacted the ease of publication of literary writings as a factual form of self-expression. Poem as a type of literature has always been popularly chosen by the public because it contains both freedom and aesthetics. This study aims to describe the framing of the Kanjuruhan tragedy-themed poem in the Jawa Pos digital media from ontology, epistemology, and axiology perspectives. This type of research is qualitative. Data analysis descriptively positioned the researcher as the main research instrument. The data collection method uses basic tapping techniques and advanced techniques in the form of notes. The analytical procedure to determine framing is done by reading the poem carefully, analyzing the framing of the poem according to Entman's approach, and summarizing the findings. The results of framing research using an Entman’s approach seen from the depth of the perspective of ontology, epistemology, and axiology show that the poem published by Jawa Pos contains the sharpness of criticism and reflection by raising solidarity on the issue of humanism which indicates the alignment of creators to victims and criticizing state institutions and those in power. These findings add to the diversity of framing research using the Entman approach with new objects in the form of literary works. These results also indicate that framing analysis can clarify the ideology of a media in terms of everything it publishes.